O-04 Deserviţi și marginalizaţi... timpul pentru schimbare. (19th November 2022) - Allen, Gemma; Jerwood, Jed
Abstract : Background: Roma communities are one of the most marginalised in the UK, experiencing systematic barriers, structural racism and health inequity that results in lower life expectancy and inequitable access to palliative care. There is little evidence of research around advance care planning and Roma people. Aims: Work in co-production to explore views and experiences of care, advance care planning, death and dying. Provide equitable advance care planning for Roma people. Methods: A co-production group was formed, including a Roma community worker who supported recruitment. Three arts-based advance care planning workshops were delivered with information translated and interpreters present. Filmed footage provided further analytical information. A reflexive thematic analysis was carried out and themes will be developed from analysis. Results: Participants expressed choices verbally and through art-making. Insight was gained from individual experiences shaped by practical, political, socio-economic and systematic barriers. Data analysis is on-going, and findings will be shared at conference. Conclusion: There are approximately 250, 000 Roma people living in the UK and there is an urgent need for providers and stakeholders to understand what is important for this community. Study findings will support inclusive and personalised palliative care. A call for action is required for services to listen and embed change to meet the diverse needs of a community who for far too long been underserved. It's time for change.